ナンキョク シュウカイ キキュウ (PPB) ショウライ ケイカク 1991-1993 - 藤井, 良一; フジイ, リョウイチ; 宮岡, 宏; ミヤオカ, ヒロシ; 門倉, 昭; カドクラ, アキラ; 小野, 高幸; オノ, タカユキ; 山岸, 久雄; ヤマギシ, ヒサオ; 佐藤, 夏雄; サトウ, ナツオ; et al. (国立極地研究所, 1989)
P(論文) 南極周回気球(Polar Patrol Balloon : PPB)計画は, 気球を成層圏内に一定高度で長時間(数週間)浮遊させ, 安定したzonalな風系に乗せて南極大陸の回りを周回させ地球物理や宇宙線・天文等の観測を行うことを目的としている。宇宙科学研究所によりその実現可能性が検討され, 国立極地研究所に提案された観測計画で, 昭和59年度より国立極地研究所, 宇宙科学研究所, 全国の共同研究者が共同して, PPBの開発を行ってきた。PPB実験を行うための工学的開発は順調に進み, この間第28次観測隊での2機の飛しょう試験も実施した。本報告では現在までに開発した工学的技術や予想されるPPBの季節・高度別飛しょう軌道, PPB実験のスケジュール及び搭載の考えられている観測機器について概略を述べる。 Since 1984 the National Institute of Polar Research, the Institute of Space and Astronautical Science and collaborative scientists have conducted the long-term circumpolar balloon program that is called Polar Patrol Balloon (PPB) project, and they also have developed ballooning technologies for this program. This project aims at establishing a station network in the stratosphere over the Antarctic region for geophysical and astrophysical observations. Two test flight experiments that were performed by the 28th Japanese Antarctic Research Expedition (JARE) in 1987 have convinced us that PPB would come back to the launching area with a good possibility. During 1991 and 1993 (JARE-32-34) at Syowa Station. The PPB experiments will consequently be done for scientific researches. This brief paper reports unique advantages of PPB, specifications and expected trajectories of PPB, and planned scientific researches with PPB. departmental bulletin paper